(untitled) (Eurasian Medical Research Periodical, 2022)
It is the most common type. Up to 66% of migraine attacks are without aura and was formerly called a classic migraine, in which the patient has five distinct typical attacks in his life and Migraines last 4 - 72 hours Purpose The research aims to determine the association and the resulting effects between family history, depression, and migraine headaches. Patient and Method Based on a cross-sectional study of 200 patients collected from different Hospitals in Iraq. In this study, migraine patients were relied upon, Primary and secondary headache patients were excluded. Result Relying on the statistical analysis program to analyze data and demographic information, a statistically significant relationship was found between family history and migraine headache patients with a p-value of 0.0045